Poly(lactic acid) : synthesis, structures, properties, processing, applications, and end of life - Auras, Rafael; Lim, Loong-Tak; Selke, Susan E. M.; Tsuji, Hideto (John Wiley & Sons, Inc., 2022)
"This updated edition brings back one of the first comprehensive guides about polylactide polymers (PLA) that has widely been considered "the PLA Bible." This book presents the structural, physical, mechanical, processing, and applications information for polylactide polymers. Opening with a summary review of PLA and its current market applications, the book is broken into sections on chemistry and production; properties and characteristics; processing and conversion; biodegradability, recycling, and sustainability; and applications in the medical, packaging, and textile industries. This new edition reflects the advanced research on PLA and includes a new chapter on the mechanical and chemical recycling of PLA as well as revised chapters that incorporate the latest studies on PLA stereocomplex, new PLA composites, the environmental footprint of PLA, and much more."-- Provided by publisher.
Keywords: Biodegradable plastics.; Lactic acid.; Polymers.; elektronické knihy; electronic books